The Effectiveness of Massage and Virgin Coconut Oil (VCO) Combination Therapy on Reducing Itching in Diabetes Mellitus - Zamroni, Amiruz; Sutawardana, Jon Hafan; Kushariyadi; Sodikin, M. (Al-Hijrah Indonesia, 2023)
Diabetic pruritus is a skin complication that is often found in diabetes mellitus patients which is characterized by complaints of itching. One of the complementary therapies that can reduce itching is to do massage and VCO combination therapy. The study aim to analyze the effectiveness of combination massage therapy and VCO to reduce itching in diabetic. This research is a descriptive study using a case study approach. Participant in this study was patient with type II diabetes mellitus with complaints of itchy skin. The intervention was carried out for 3 days of treatment with a frequency of action twice a day in the morning and evening after bathing. The pre-test and post-test were assessed using two instruments including the Overall Dry Skin Score (ODSS) to assess the dryness of the patient's skin and the Itch Numeric Rating Scale (Itch NRS) to assess the patient's itch level. The results showed a decrease in the level of skin dryness from the scale 3 to scale 2 on day 3 of treatment and there was a decrease in the itching scale from scale 7 to scale 4 on day 3 of treatment. Combination therapy of massage and VCO can increase the level of skin moisture as evidenced by a decrease in the level of skin dryness so that it will also reduce the level of skin itching. With these results, it can be considered to make combination massage therapy and VCO as therapeutic modality to overcome the problem of itching in DM patients.